Next Generation Sequencing of Sporadic Vestibular Schwannoma: Necessity of Biallelic NF2 Inactivation and Implications of Accessory Non-NF2 Variants. Issue 9 (October 2018) - Carlson, Matthew L.; Smadbeck, James B.; Link, Michael J.; Klee, Eric W.; Vasmatzis, George; Schimmenti, Lisa A.
Abstract : Objectives: 1) Describe the genetic alterations discovered in a series of sporadic vestibular schwannomas (VS). 2) Identify if more clinically aggressive variants possess different genetic alterations compared to more indolent-behaving VS. Methods: Fresh frozen tumor and matched peripheral blood leukocytes from 23 individuals with sporadic VS were analyzed using whole-exome sequencing, tumor whole transcriptome expression profiling (mRNA-Seq), and tumor mate-pair analysis. Source cases included tumors with fast preoperative growth, giant tumors in young patients, tumors with macrocystic change, recurrent tumors following radiation or microsurgery, and indolent small tumors with minimal or no growth before surgery. Somatic and germ-line alterations of the NF2 gene and beyond the NF2 locus were identified and analyzed using complementing analyses. Results: Biallelic somatic events involving the NF2 gene were discovered in every analyzed tumor specimen with no concurrent NF2 variants identified in matching peripheral blood specimens. Thirteen tumors showed loss of one chromosome 22 (ch22), 4 tumors showed copy-neutral 22q loss of heterozygosity, and 31 unique small variants in the NF2 gene were discovered. Of the latter, 10 were essential splice site, 11 frame shift, 7 stop gain, 2 missense, and 1 in-frame mutation. No other common or recurring NF2 mutations were identified. However, several other notable large chromosomal aberrations were discovered including 2 tumors with loss of a chromosome 21, 3 with loss of an X or Y chromosome, 1 with copy-neutral loss of heterozygosity in chromosome 15, and 1 with loss of 18p and 16q. All of these other major chromosomal abnormalities only occurred in tumors demonstrating a more aggressive phenotype. Conclusions: To date, few studies have used whole-exome sequencing, mate-pair analysis, and RNA-seq to profile genome-wide alterations in sporadic VS. Using high-throughput deep sequencing, "two-hit" alterations in the NF2 gene were identified in every tumor and were not present in peripheral blood supporting that all events were somatic. Type of NF2 gene alteration and accessory mutations outside the NF2 locus may predict phenotypic expression and clinical course.